A year of movies : 365 films to watch on the date they happened - Walters, Ivan, 1963- (Rowman & Littlefield, 2016)
This book lists 365 films, one for each day of the year, organized by the date on which at least one scene in the movie occurs on that date. For example, The Longest Day, a movie about the 1944 Normandy invasion, is the entry for June 6. For some films the scene that occurred on the date only lasts a few moments, but is pivotal to the film; for others it takes up most of the film's running time. The entries note the time in which the representative scene takes place, as well as the evidence for the film choice-either the time in the film when the date is referenced or a source that cites the d.